Diet of the tawny owl (Strix Aluco) in the karst environment near Škocjanske jame (SW Slovenija) - Lipej, Lovrenc (Acta carsologica, 1996)
The diet of the Tawny Owl (Strix aluco) was studied in karst area near Škocjanske jame (Škocjan Caves) in the southwestern part of Slovenia. Pellets were collected during the 1992-1993 period in the cave entrance in the submediterranean forest belt. The dominant prey group was the Fat Dormouse (Myoxus glis), 37.7% by number and 83.5% by weight. Insects were the most important alternative prey. Seasonal variations in the diet are also discussed.
Keywords: food; karst; Kras; prehrana; sove